2001
DOI: 10.2169/internalmedicine.40.1245
|View full text |Cite
|
Sign up to set email alerts
|

Portal and Mesenteric Vein and Inferior Vena Cava Thrombosis Associated with Antiphospholipid Syndrome.

Abstract: Wereport a 48-year-old man with thrombosis of the portal and superior mesenteric vein and inferior vena cava associated with primary antiphospholipid syndrome (APS). Primary APSwas diagnosed by a positive reaction with anticardiolipin antibody (aCL) and the absence of any evidence suggesting the presence of other disease states known to be associated with aCL. A coeliac angiography showed obstruction of the portal and superior mesenteric vein with prominent collaterals and cavernous transformation. Femoral vei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…13 It has also been reported that portal vein thrombosis often develops as a result of APS. [14][15][16] In the current case, portal hypertension seemed to be induced by portal vein thrombosis, which was possibly caused by APS that slowly developed 5 years after the onset of BCC. Irregular distribution of pulmonary circulation might be also associated with APS.…”
Section: Discussionmentioning
confidence: 61%
“…13 It has also been reported that portal vein thrombosis often develops as a result of APS. [14][15][16] In the current case, portal hypertension seemed to be induced by portal vein thrombosis, which was possibly caused by APS that slowly developed 5 years after the onset of BCC. Irregular distribution of pulmonary circulation might be also associated with APS.…”
Section: Discussionmentioning
confidence: 61%
“…There are several cases in the literature of great vein thrombosis (inferior vena cava, portal vein or mesenteric vein) in the presence of antiphospholipid antibodies 7,8 but superior vena cava involvement has not been described.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombosis of the mesenteric vein was first described by Warren and Eberhard [11] in 1935 and there have been several case reports of mesenteric vein thrombosis associated with aCL antibodies [12]. Portal and superior mesenteric [13].…”
Section: Discussionmentioning
confidence: 99%